The Role And Responsibilities Of Women In The Legal And Ritual Tradition Of Muslim Society - Muswar Sikandar Makol; Prof.Dr.Matloob Ahmad(Corresponding Author); Dr. Talib Ali Awan (International Research Journal of Arabic and Islamic Studies, 2024)
The role and responsibilities of women in Muslim society have been deeply embedded in both legal frameworks and ritual traditions derived from Islamic teachings. This exploration sheds light on the dynamic and evolving nature of women’s participation in various spheres of life, as guided by religious texts, jurisprudence, and cultural practices.Islamic legal traditions, rooted in the Qur'an and Hadith, have historically emphasized the importance of safeguarding women's rights. Women are granted clear entitlements, including the right to inheritance, property ownership, and financial independence. For example, the Qur'an specifies shares of inheritance for women, reflecting their recognized role in the economic fabric of society. Additionally, women possess the right to enter into and dissolve marriage, underscoring their agency in personal and familial matters. Despite these provisions, the practical application of women’s legal rights has often been influenced by cultural interpretations and societal norms. Variations in these practices across different Muslim societies highlight the tension between religious doctrine and local customs. For instance, while some regions have advanced gender-equitable policies in line with Islamic teachings, others have perpetuated restrictive interpretations that limit women’s participation in public and private spheres.Women hold a significant place in the ritual practices of Islam, participating in acts of worship such as prayer (Salah), fasting (Sawm), almsgiving (Zakat), and pilgrimage (Hajj). These rituals underscore the spiritual equality of men and women, as articulated in the Qur'an: “Whoever does righteous deeds, whether male or female, while being a believer—such will enter Paradise”. However, certain ritual responsibilities are uniquely tailored to women, reflecting their specific roles within the family and community. For instance, women’s responsibilities in nurturing children and maintaining familial bonds are often viewed as extensions of their spiritual obligations. The concept of “Jannah lies under the feet of mothers” (Hadith) exemplifies the elevated status of women in fulfilling these duties.Historically, Muslim women have played prominent roles as scholars, leaders, and activists. Figures such as Aisha bint Abu Bakr, a respected Hadith scholar, and Fatima al-Fihri, the founder of the world’s first university, serve as enduring examples of women’s intellectual and social contributions.In contemporary times, debates around women’s roles in Muslim societies continue to evolve. Issues such as education, employment, and political participation are central to these discussions, with many advocating for reforms that align cultural practices with the egalitarian principles of Islam. Initiatives promoting women’s empowerment through Islamic frameworks have gained traction, emphasizing the compatibility of faith and gender equity.The roles and responsibilities of women in the legal and ritual tradition of Muslim society are both profound and complex. While Islamic teachings provide a foundation for women’s rights and spiritual equality, the interpretation and implementation of these principles remain subject to historical and cultural influences. Recognizing and addressing these challenges is essential for fostering a more inclusive understanding of women’s roles in contemporary Muslim societies. By revisiting and reaffirming the core values of justice and equity in Islam, women can continue to play a transformative role in both religious and societal contexts.